UWRF CAFES internship program evaluation, 2014 - Halopeka, Taylor; Spaeth, Kaylin; Trechter, David; Parks, Denise (My University, 2014)
The motivation for this study was to evaluate intern experiences of the College of Agriculture, Food and Environmental Sciences (CAFES) students at the University of Wisconsin-River Falls (UWRF). The CAFES Internship Office wanted to understand and improve the internship experience of CAFES students.
58 p.
Keywords: University of Wisconsin-River Falls. College of Agriculture, Food and Environmental Sciences; College students--Wisconsin--River Falls; University of Wisconsin-River Falls--Students; Internship programs--Evaluation; University of Wisconsin-River Falls; Interns--Wisconsin--River Falls; College students